Bacterial colonization of resin composite cements: influence of material composition and surface roughness. (15th June 2017) - Glauser, Stephanie; Astasov‐Frauenhoffer, Monika; Müller, Johannes A.; Fischer, Jens; Waltimo, Tuomas; Rohr, Nadja
Abstract : So‐called secondary caries may develop in the cement gap between the tooth and the bonded restoration. Cement materials with a low susceptibility to biofilm formation are therefore desirable. In the present study, the adhesion of Strepococcus mutans onto three adhesive (Multilink Automix, RelyX Ultimate, and Panavia V5) and three self‐adhesive (Multilink Speed Cem, RelyX Unicem 2 Automix, and Panavia SA plus) resin composite cements was evaluated. Previous studies have failed to evaluate concomitantly the effect of both the composition of the cements and their surface roughness on biofilm formation. The presence of S. mutans on cement surfaces with differing degrees of roughness was therefore recorded using fluorescence microscopy and crystal violet staining, and the composition of the cements was analyzed using energy‐dispersive X‐ray spectroscopy mapping. Biofilm formation on resin composite cements was found to be higher on rougher surfaces, implying that adequate polishing of the cement gap is essential. The use of copper‐containing cements (Multilink Automix, Panavia V5, and Panavia SA plus) significantly reduced biofilm formation.